2004
DOI: 10.3732/ajb.91.1.125
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeny of all species of Arceuthobium (Viscaceae) using nuclear and chloroplast DNA sequences

Abstract: The genus Arceuthobium (dwarf mistletoes, Viscaceae) comprises 42 species that parasitize hosts in Pinaceae and Cupressaceae in the Old and New Worlds. Maximum parsimony analyses were conducted on two data partitions (separately and combined): nuclear ribosomal internal transcribed spacer (ITS) sequences for all 42 currently recognized species and chloroplast trnT-L-F sequences for 34 New World species. The Old and New World species were phylogenetically distinct using ITS, thus making subgenus Arceuthobium pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 56 publications
(69 reference statements)
2
33
0
Order By: Relevance
“…It was proposed (91,92) that this mistletoe could be primitive (i.e., evolved early in the history of the genus) and was thus the "link" to other members of Viscaceae that have nondehiscent fruits. The topology of the molecular phylogenetic tree clearly showed that this was not the case (152). The ancestor of A. verticilliflorum had an explosive fruit, but this feature was lost sometime during the evolution of the modern species.…”
Section: Corymbosus) Andmentioning
confidence: 97%
See 1 more Smart Citation
“…It was proposed (91,92) that this mistletoe could be primitive (i.e., evolved early in the history of the genus) and was thus the "link" to other members of Viscaceae that have nondehiscent fruits. The topology of the molecular phylogenetic tree clearly showed that this was not the case (152). The ancestor of A. verticilliflorum had an explosive fruit, but this feature was lost sometime during the evolution of the modern species.…”
Section: Corymbosus) Andmentioning
confidence: 97%
“…The first molecular phylogenetic investigation of interspecific relationships in dwarf mistletoes was by Nickrent et al (154) using ITS sequences. A second more detailed study included all currently recognized species in the genus and added chloroplast (trnL region) sequences to the ITS data (152). That study showed that the Old and New World species were genetically distant, so much so that primers for the trnL region did not work with the Old World taxa.…”
Section: Corymbosus) Andmentioning
confidence: 99%
“…& Wiens, an endemic to the Azores, is said to be "crucial to an understanding the migrational history of the genus" (Nickrent et al 2004). The species is also characterized by verticillate branching, as are the related A. oxycedri (DC.)…”
Section: F 2-1d) Is Incorrect)mentioning
confidence: 99%
“…Forty-two spp. (according to Nickrent et al 2004); one sp. on Hispaniola, and one on the Azores; various spp.…”
Section: Viscaceae and Human Society Medicinal Aspectsmentioning
confidence: 99%
“…Curiously, in the rare instances that these mistletoes become established on uncongenial hosts, as in A. americanum on Picea engelmannii, an anisophasic broom develops; the symptomatolgy has changed radically. Isophasic parasitism in Arceuthobium likely evolved independently more than once, as suggested by its documented occurrence in both subgenera and four sections recognized by Nickrent et al (2004). In addition to the remarkable Mexican Phoradendron perredactum that has recently been described (Kuijt 2011;Rzedowski and Calderón de R. 2011), parallels to this mode of parasitic behavior have evolved independently in some holoparasitic plants in Apodanthaceae (Pilostyles haussknechtii) and Mitrastemonaceae (Mitrastemon) (Kuijt 1960).…”
mentioning
confidence: 99%